The Effectiveness of STEAM Learning Based on â€œRobotisâ€ Projects to Improve Science Literacy of Elementary School Students - Nadia Lutfi Choirunnisa; Suryanti; Desi Rahmawati; Mulyani Mulyani (Jurnal Penelitian Pendidikan IPA, 2023)
In the industrial revolution era, many jobs that humans could initially do turned out to be done by computers and machines. Learning in elementary schools should be carried out by integrating various disciplines, for example, through project-based STEAM learning. STEAM learning incorporates the contents of Science, Technology, Engineering, Art, and Mathematics. The STEAM project chosen for implementation is Robotis (Robot Tisu/Tissue Robot). This study aims to describe the STEAM learning design of the Robotis project and determine the effectiveness of project-based STEAM learning in improving science literacy skills. This research includes a quasi-experiment with a one-group pretest-posttest design. The study was conducted at SD A (one of the private schools in Surabaya) with an experimental class subject of 15 students and a control class subject of 13 students. The instruments used are validation sheets of teaching modules and science literacy tests. Data were analyzed using the n-gain test and the Mann Whitney U-Test. The results showed that STEAM learning design must integrate several disciplines (science, technology, engineering, art, mathematics) in one learning and be associated with real-world problems. The significance value is 0.00 < 0.05 so that it is interpreted that there is a difference between the two groups (H1 accepted) which means that STEAM learning in the experimental class provides different results between pre-test and post-test. So, it can be stated that STEAM learning is effective for improving students' science literacy skills.